Enhancing social functioning using multi-user, immersive virtual reality - D. J. Holt; N. R. DeTore; B. Aideyan; L. Utter; L. Vinke; D. S. Johnson; J. Zimmerman; K. N. Dokholyan; A. Burke (Scientific Reports)
Abstract Rates of loneliness and other forms of social disconnection have been increasing worldwide. Prior studies have suggested that brief behavioral interventions can teach skills that may improve social functioning and connection but, currently, access to such interventions is limited. One previously untested approach for addressing this gap is to teach these skills using immersive, multi-user virtual reality (VR). To measure the feasibility of this approach, 33 young adults experiencing social discomfort were enrolled in a study of a VR-based application called Reconnecting with Ourselves and Others in virtual Meetings (ROOM), which delivered a previously validated, mindfulness-based intervention. Satisfaction ratings, qualitative feedback, and quantitative measures of aspects of social functioning, including social comfort, interpersonal distance, and facial affect recognition, were collected from participants. All of the participants attended more than half of the sessions and 90.3% found ROOM to be beneficial and useful. In addition, comfort with others in the real world (p = 0.02) and facial affect recognition accuracy (p = 0.02) significantly increased, while interpersonal distances remained unchanged, following ROOM. An immersive, multi-user VR intervention may represent one feasible, scalable approach for disseminating skills that can improve social functioning and connection. Trial registration Clinicaltrial.org # NCT06360562.